Design–Cost Nexus of Rapid Sand Filter Systems in Water Supply Projects: A Comparative Construction Management Analysis from Nepal - Khanal, Sarita; Dahal, Khetraj; Gyawali, Prakash (International Journal on Engineering Technology, 2026)
Rapid Sand Filters (RSFs) are the dominant treatment technology in Nepalese water supply projects, yet similar-capacity systems exhibit markedly different construction costs, suggesting inconsistent design practices and poor cost efficiency. Methods: This study employs a mixed-methods approach—combining quantitative analysis of design drawings, hydraulic data, Bills of Quantities (BOQs), and cost estimates with qualitative insights from field observations and expert interviews—across four completed water quality improvement projects in Sindhupalchowk and Kavrepalanchowk districts. Key design parameters (filter bed area, structural depth, RCC volume, reinforcement quantity, filter media, underdrain system) were systematically compared and a simple linear regression was performed to quantify the reinforcement–cost relationship. Results: Total construction costs ranged from NPR 1.91 million to NPR 6.11 million. Civil works constituted 48–58% of cost in three projects; mechanical and electrical works dominated Project D at 77.8%. Reinforcement quantity explained 96.9% of cost variation (R² = 0.969; p = 0.016), with a unit rate of NPR 150 per kg. Conservative structural detailing and absence of standardized design norms are identified as the primary sources of cost disparity. Conclusion: Rationalising structural depth and reinforcement specifications through context-sensitive design guidelines can substantially reduce RSF construction costs without compromising treatment performance.